A heroína mais forte da terra: Carol Danvers e o feminismo nas HQ’s norte-americanas - Rocha, Bruna Amanda Godinho (Universidade do Vale do Rio dos Sinos, 2021)
This study investigates female representation in American superhero comics, analyzing the trajectory of the character Carol Danvers - as Ms. and Captain Marvel. To support this research, I used studies about the feminist movement, its impacts on society, with emphasis on some women. Also, it was necessary to undertake a discussion of the concept of cultural industry - as the comics are in this production logic, to establish, critically, the dialogue between the feminist movement, the comics universe, and the cultural industry. In general, since the emergence of contemporary comics, social, political, and cultural aspects have been debated within them. However, since the 60's, due to the growing academic interest is that they became analyzed as artistic expression, with critical possibilities, maintenance, or subversion of the models traditionally produced and established. The proposal is to study the changes that Carol Danvers has throughout her journey and reflect on how they connect to the feminist movement. We eager to contribute and expand the discussion of the cultural industry impact on the dynamics and struggles of society.
Keywords: Cultura quadrinesca; Marvel Comics; Carol Danvers; Feminismo; Representação; Comics culture; Feminism; Representation; ACCNPQ::Ciências Humanas::História